2022
DOI: 10.1139/cjss-2021-0080
|View full text |Cite
|
Sign up to set email alerts
|

Impact of conservation tillage on runoff, soil loss, and soil properties on acrisols and ferralsols in central Benin

Abstract: The present study is aimed at assessing the impact of different tillage practices and mulch input rates on soil erosion and soil properties in Central Benin. The experiment was carried out at two sites (Dan and Za-zounmè) using a randomized complete block design. The effect of three tillage practices: contour ridging (CR); slope ridging (SR) and no-tillage (NT) and four mulch input rates (0 t.ha-1; 3 t.ha-1; 5 t.ha-1, 7 t.ha-1) were investigated. The runoff, the soil and nutrients losses were measured during t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 45 publications
0
10
0
Order By: Relevance
“…The furrow serves as a means for directing runoff water, leading to high soil erosion. A growing body of research over the past few years has shown that CR can significantly curb water erosion compared with SR (Akplo et al., 2022; Barton et al., 2004; Shi et al., 2004; Stevens et al., 2009). The review of the literature on NT or minimum tillage suggests that they typically result in a significant reduction in surface runoff and sediment losses (Quinton & Catt, 2004; Ryken et al., 2018; Silgram & Shepherd, 1999; Strauss et al., 2003).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The furrow serves as a means for directing runoff water, leading to high soil erosion. A growing body of research over the past few years has shown that CR can significantly curb water erosion compared with SR (Akplo et al., 2022; Barton et al., 2004; Shi et al., 2004; Stevens et al., 2009). The review of the literature on NT or minimum tillage suggests that they typically result in a significant reduction in surface runoff and sediment losses (Quinton & Catt, 2004; Ryken et al., 2018; Silgram & Shepherd, 1999; Strauss et al., 2003).…”
Section: Discussionmentioning
confidence: 99%
“…In Benin forest destruction, land overexploitation and unsuitable agricultural practices have contributed to great land degradation (Avakoudjo et al., 2021). As a result, most of the agroecological zones in Benin are characterized by high erosion (Akplo et al., 2022). Erosion results in declining soil fertility and decreasing crop yields (Saïdou et al., 2012).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, potential trade‐offs tend to be lower in agroecosystems with adequate precipitation or irrigation, high levels of inputs, mechanization, and greater crop production allowing enough CR for different uses (Erenstein et al, 2012). Several researches have shown that maintaining CR is a good farming practice (Akplo et al, 2022; Traoré et al, 2020). One key principle of conservation agriculture is the maintenance of CR on fields as mulch‐alternative options such as cover crops imply extra costs and challenges (Erenstein, 2002).…”
Section: Trade‐offs In Crop Residue Usementioning
confidence: 99%
“…Soil erosion reduction effect of no-tillage practice has been documented frequently and is mostly attributed to increased organic carbon content and the retention of crop residues at the soil surface [46]. Appropriate tillage is considered an important management tool to combat water erosion risks, promote in situ water conservation, improve crop yields and stabilize rainfed agricultural systems [6].…”
Section: Soil Erodibilitymentioning
confidence: 99%
“…While water and wind are the main causes of soil erosion, soil losses by water are more serious than those by wind [3]. Africa hosts more than 45% of the total erosion affected people [4] where it affects millions of hectares of soil [5] [6].…”
Section: Introductionmentioning
confidence: 99%